2014
DOI: 10.1007/s12402-014-0139-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ADHD symptomatology and self-harm, suicidal ideation, and suicidal behaviours in adults: a pilot study

Abstract: The aim of this study was to explore whether individuals with attention-deficit/hyperactivity disorder (ADHD) are at risk of harm over the lifespan due to increased rates of self-harm, suicidal ideation and suicidal behaviour, and whether this association is mediated by psychosocial factors. Sixty-six adults (43 men, 23 women; 18-65 years) participated in this study involving clinical interview and retrospective self-report measures of ADHD symptoms, self-harm/suicidal behaviour, mental health disorders, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Suicidality in ADHD patients who have psychiatric comorbidity: From the 26 papers of this review, the 10 studies, which investigated comorbidity in ADHD patients with suicidality are presented in Table 4[27,28,35-39,47,48]. …”
Section: Resultsmentioning
confidence: 99%
“…Suicidality in ADHD patients who have psychiatric comorbidity: From the 26 papers of this review, the 10 studies, which investigated comorbidity in ADHD patients with suicidality are presented in Table 4[27,28,35-39,47,48]. …”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature here again indicated contradictory findings. While there were studies observing no difference between bipolar patients with and without ADHD comorbidity in terms of suicide attempt history (15,23), others reported significantly more suicide attempts in the group with comorbidity (11,30,33,34,35). Since the patients diagnosed with both diseases experience impulsivity, difficulty in controlling themselves, and negative life events more frequently, suicide attempts may be expected (36).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent ADHD also differed significantly from comparsion groups (transient ADHD and control) in NSSI frequency, variety and severity (Cohen’s d: 0.32–0.87; p  < 0.05). Externalizing symptoms mediate between ADHD and NSSI (IE = 0.29; SE = 0.11; CI 95%: 0.10–0.51).Taylor et al (2014) [44]New-Zealandcase–control study, patients with retrospective ADHD and control groupM = 31.9; SD = 1.666 (35 with adult ADHD and 31 with no ADHD)DSHYesquestionnaire for DSH; DSHISignificant associations were present between ADHD symptom severity and history of self-harm behaviour, suicidal ideation and suicide attempts. These relationships were mediated by comorbidity (mood, anxiety, drug and alcohol abuse disorders) and emotion-focused coping style.…”
Section: Methodsmentioning
confidence: 99%